Phytic acid accumulation in plants: Biosynthesis pathway regulation and role in human diet - Silva, Vinicius Martins [UNESP]; Putti, Fernando Ferrari [UNESP]; White, Philip J.; Reis, André Rodrigues dos [UNESP] (Elsevier, 2021)
Phytate or phytic acid (PA), is a phosphorus (P) containing compound generated by the stepwise phosphorylation of myo-inositol. It forms complexes with some nutrient cations, such as Ca, Fe and Zn, compromising their absorption and thus acting as an anti-nutrient in the digestive tract of humans and monogastric animals. Conversely, PAs are an important form of P storage in seeds, making up to 90% of total seed P. Phytates also play a role in germination and are related to the synthesis of abscisic acid and gibberellins, the hormones involved in seed germination. Decreasing PA content in plants is desirable for human dietary. Therefore, low phytic acid (lpa) mutants might present some negative pleiotropic effects, which could impair germination and seed viability. In the present study, we review current knowledge of the genes encoding enzymes that function in different stages of PA synthesis, from the first phosphorylation of myo-inositol to PA transport into seed reserve tissues, and the application of this knowledge to reduce PA concentrations in edible crops to enhance human diet. Finally, phylogenetic data for PA concentrations in different plant families and distributed across several countries under different environmental conditions are compiled. The results of the present study help explain the importance of PA accumulation in different plant families and the distribution of PA accumulation in different foods.
Keywords: Anti-nutrient; Inorganic phosphorus; Inositol-phosphate; Myo-inositol; Phytase; Phytic acid